Group-centric attitudes mediate the relationship between need for closure and intergroup hostility. (December 2018) - Dugas, Michelle; Schori-Eyal, Noa; Kruglanski, Arie W.; Klar, Yechiel; Touchton-Leonard, Kate; McNeill, Andrew; Gelfand, Michele J.; Roccas, Sonia
A model of the relationship between need for closure (NFC) and intergroup hostility was tested in four studies. According to the model, heightened NFC promotes glorification of the ingroup which fosters support for extreme measures against the group's perceived enemies. In a parallel process, high level of NFC induces perceptions of ingroup victimhood, which also adds support for aggressive actions toward rival outgroups. In the first two studies, conducted in Palestine's West Bank (Study 1) and in the United States (Study 2), NFC promoted a greater sense of moral entitlement to engage in violence against the outgroup, and this was mediated by perceived ingroup victimhood. The subsequent two studies tested the full hypothesized parallel mediation model among students in Northern Ireland (Study 3) and Jewish-Israelis (Study 4). Results largely supported the proposed model. Findings are discussed in relation to additional evidence linking NFC to phenomena of intergroup hostility.